Elevated Serum and Cerebrospinal Fluid CD138 in Patients With Anti-N-Methyl-d-Aspartate Receptor Encephalitis - Zhu, Jiajia; Li, Yongqi; Zheng, Dong; Wang, Zhanhang; Pan, Suyue; Yin, Jia; Wang, Honghao (Frontiers in Molecular Neuroscience, 2019)
Background CD138 (also known as syndecan-1) is an important component of endothelial cell glycocalyx, and it is reportedly involved in negative regulation of various inflammatory processes. The clinical implications of circulating and cerebrospinal fluid (CSF) soluble CD138 (sCD138) in patients with Anti-N-methyl-d-aspartate receptor (NMDAR) encephalitis remain unclear. Objective The aim of the current study was to investigate associations between serum and CSF sCD138 levels in anti-NMDAR encephalitis patients. Methods The participants enrolled in the study included 27 with anti-NMDAR encephalitis, 11 with viral meningoencephalitis, and 22 controls. At acute stage and 3 to 6-month follow-up time-points, sCD138, tumor necrosis factor-α, matrix metalloproteinase-2, and matrix metalloproteinase-9 in serum and CSF were measured in all participants via enzyme-linked immunosorbent assays. Results Serum and CSF levels of sCD138 were significantly increased in patients with anti-NMDAR encephalitis. Furthermore, after 3–6 months of follow-up CSF sCD138 levels were significantly decreased in anti-NMDAR encephalitis patients. Changes in sCD138 levels were significantly associated with amelioration of modified Rankin Scale scores in patients with anti-NMDAR encephalitis. Conclusion In anti-NMDAR encephalitis patients, high circulating, and CSF sCD138 is associated with inflammation and poor clinical prognosis. The present study suggests that sCD138 may be an informative biomarker of inflammation in anti-NMDAR encephalitis.